Attitude, Change, Competitiveness (Confluenţe Bibliologice, 2021)
The author refers briefly to the activity of Mrs. Elena Harconiţa as a librarian (since 1976) and Director of the USARB Scientific Library in Balti, during the period 2001- 2020. Almost 20 years (if we take into account the intensity of the director's work), Mrs. Elena Harconiţa managed to fit into the Balti academic community as well as in the national professional environment, through individuality, multiple professional and managerial preoccupations.
Keywords: further training